2018
DOI: 10.3390/f10010004
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effect of Different 24-epiBL Pretreatments on Salinity Tolerance in Robinia pseudoacacia L. Seedlings

Abstract: As a brassinosteroid (BR), 24-epibrassinolide (24-epiBL) has been widely used to enhance the resistance of plants to multiple stresses, including salinity. Black locust (Robinia pseudoacacia L.) is a common species in degraded soils. In the current study, plants were pretreated with three levels of 24-epiBL (0.21, 0.62, or 1.04 µM) by either soaking seeds during the germination phase (Sew), foliar spraying (Spw), or root dipping (Diw) at the age of 6 months. The plants were exposed to salt stress (100 and 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Similar results were also recorded in potatoes through BRS priming subjected to salinity stress which indicates the positive role of BRS in metigating the negative impact of salt stress on lipid peroxidation level (Efimova et al, 2018). Yue et al (2018) also reported that pretreatment of BRS declines the MDA content in Robinia pseudoacacia L. under salinity stress.…”
Section: Effect Of Brss On Mda Content Under Salinity Stresssupporting
confidence: 74%
“…Similar results were also recorded in potatoes through BRS priming subjected to salinity stress which indicates the positive role of BRS in metigating the negative impact of salt stress on lipid peroxidation level (Efimova et al, 2018). Yue et al (2018) also reported that pretreatment of BRS declines the MDA content in Robinia pseudoacacia L. under salinity stress.…”
Section: Effect Of Brss On Mda Content Under Salinity Stresssupporting
confidence: 74%
“…The relative water content in the leaves was measured according to the previously method [19] using the following formula: RWC = (fresh weight − dry weight)/(turgor weight − dry weight. The membrane stability index was estimated using the formula [20], MSI = 1 − C1/C2, where C1 is the electrical conductivity bridge after the leaves were heated at 40 • C for 30 min in a water bath, and C2 is the electrical conductivity bridge after the leaves were boiled at 100 • C for 10 min in a water bath.…”
Section: Leaf Water Status and Membrane Stability Indexmentioning
confidence: 99%
“…An overabundance of ROS, which cannot be compensated by antioxidative systems, leads to damage symptoms such as chlorophyll degradation, membrane leakage, and eventually necrosis [13]. Some examples for salt damage symptoms at the tissue and organelle levels are also demonstrated in this Special Issue [14,15]. Since soil degradation with enhanced salinization is an increasing problem, identification of salt-tolerant plant species and measures to enhance the resistance of crops and horticultural plants are urgently needed.…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 96%
“…The beneficial effect was concentration dependent and disappeared in plants exposed to 1 mM salicylic acid. In another study, Robinia pseudoacacia seeds or seedlings were treated with 24-epibrassinolide (a brassinosteroid) and subsequently exhibited enhanced antioxidative protection and enhanced salt tolerance [14]. To obtain deeper insights into the signal transduction pathway activated by stress, the TCP15 transcription factor (TEOSINTE BRANCHED1, CYCLOIDEA, and PROLIFERATION CELL FACTOR) was isolated from Fraxinus mandshurica (Mandchurian ash) [21].…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 99%